Distributed shared memory system with variable granularity - Itzkovitz, Ayal; Schuster, Assaf (2002)
A method for controlling access to a physical memory in a distributed shared memory system (DSM) includes selecting a page of the physical memory in which to store a plurality of data items, including at least first and second data items. The selected page of the physical memory is divided into a plurality of minipages, including at least first and second minipages containing the first and second data items, respectively. First and second virtual pages are mapped to the selected page of the physical memory, such that the first and second virtual pages are associated respectively with the first and second minipages, with first and second access permissions applied to the first and second virtual pages, respectively. A process is permitted to access the first data item subject to the first access permission and the second data item subject to the second access permission, via the respective first and second virtual pages.